The safety standard of toys in Malaysia: towards a comprehensive toys safety system in Malaysia for consumer protection / Afifah Shakirah Baharudin and Nurul Emelda Jamel - Baharudin, Afifah Shakirah; Jamel, Nurul Emelda (2007)
This project paper is regarding with toys safety standard as well as bringing to light the potential hazards of toys. Besides discussing on toys safety standards, this project paper will also touch on the available laws that govern consumer protection. This project paper is divided into five main chapters; introduction on toys safety and consumers, general safety requirements of toys and the dangers and hazards of toys, the Malaysian safety standard and laws governing consumer protection, toys safety standards in other countries and the conclusion and recommendations. The aim of this project paper is to give an overview on the available toys safety standards in Malaysia and reviewing the standards available in other countries. It will also outline the potential dangers and hazards of toys, such as; choking, strangulation, poisoning from toxic chemicals in toys, blindness from projectiles, deafness from excessively loud toys, and cuts and burns from sharp or flammable toys. It was discovered earlier in the research that Malaysia does not have a specific mandatory safety standard with regards to toys that manufacturers must comply to. As such, this project paper will also provide suggestions and recommendations towards a comprehensive toys safety system. We hope that this project paper will be beneficial and enlightening to readers as well as able to raise more awareness among consumers.